Habituation and wonder: embodied knowledge in Renaissance Italy’s memory - Lucia Delaine (Ágora, 2022)
Renaissance techniques of memorization utilize the body, intentionally and precisely, to enhance memorization. The analysis of three Italian memory manuals from the late 1500 highlights an impressive expertise of the unique possibilities offered by an embodied acquisition of knowledge. Some concepts from current cognitive theory will help appreciate the efficacy and complexity of such techniques. This interdisciplinary reflection contributes to the delineation of a pre-Cartesian conception of human cognition.